Does unemployment matter? Economic insecurity, labour market policies and the far-right vote in Europe - Vlandas, T; Halikiopoulou, D (Palgrave Macmillan UK, 2018)
What is the impact of unemployment on far-right party support? This article develops a framework that links unemployment to far-right party support, while taking into account both the heterogeneity of the workforce and the role of labour market policies. More specifically, we focus on unemployment as a driver of economic insecurity and examine its effect on outsider and insider labour market groups. We identify the extent to which two labour market policies—unemployment benefits and Employment Protection Legislation (EPL)—mediate the effect of unemployment on economic insecurity, thus limiting the impact of unemployment on far-right party support. We carry out a large N analysis on a sample of 14 Western and 10 Eastern European countries between 1991 and 2013. We find that unemployment only leads to higher far-right support when unemployment benefits replacement rates are low. The results with regard to the mediating effect of EPL are more complex as EPL only mediates the impact of unemployment when we take into account the share of foreign-born population in the country.